Management of Moderate-to-Severe Atopic Dermatitis in Adults: A Cross-Sectional Survey of Dermatologists Within the Asia-Pacific Region - Chia-Yu Chu; Yung Chan; Siriwan Wananukul; Hao Cheng; Nisha Suyien Chandran; Ramesh Bhat; Sang Wook Son; Han-Fang Liao; Sean Gardiner; Qi Qing Ng; See-Hwee Yeo; Sophie Bozhi Chen; et al. (Adis, Springer Healthcare, 2024)
Abstract Introduction Limited evidence is available on real-world management of atopic dermatitis (AD) among Asian adults. This cross-sectional study aimed to assess current approaches in AD diagnosis and management in Asia. Methods Practising dermatologists regularly treating patients with moderate-to-severe AD were recruited from eight Asia-Pacific territories, namely Mainland China, Hong Kong, India, Japan, Singapore, South Korea, Taiwan, and Thailand. A survey was administered to eligible dermatologists after screening and taking informed consent. Data from fully completed submissions were analysed using descriptive statistics. The study was reviewed by the institutional review board in each territory. Results Data from 271 dermatologists were included for analysis. About one-third (31.7%) reported that they referred to the Hanifin and Rajka criteria during diagnosis. The majority of dermatologists used clinical impression when assessing AD severity and treatment response. Reduction of eczema and pruritus was the primary treatment objective when managing both acute (98.1%) and chronic (69.1%) AD. More than half of dermatologists preferred adding systemic anti-inflammatory medication for patients who did not respond to maximized topical treatment, while 43.6% would switch to another systemic medication for those failing to respond to maximized systemic treatment. Topical corticosteroids were frequently selected by dermatologists. For systemic therapies, oral corticosteroids were most frequently used, followed by cyclosporin and dupilumab. Narrow-band ultraviolet B was the most common phototherapy reported (84.9%). There was considerable variation in estimated average and maximum durations of therapies used to treat AD. Conclusion This study has provided insights on the real-world management of moderate-to-severe AD in the Asia-Pacific region. The diverse approaches in diagnosis and treatment highlight the multifactorial nature of AD, reliance on clinical judgement, and importance of personalized care. To improve outcomes in patients with AD, it will be crucial to develop biomarkers for diagnosis, reduce subjectivity in assessment, as well as promote access to newer and effective therapies.